How a Philosophical Approach to Temporal Perception Can Provide a Basis for Developing Useful Strategies for Teaching Art to Students with ADHD - Hirst, Barbara (Canadian Review of Art Education / Revue canadienne d'éducation artistique)

(untitled) (Canadian Society for Education through Art, 2022)
This paper explores research in how students with Attention Deficit HyperactiveDisorder (ADHD) experience temporality. Using a phenomenological lens, the author looks forclues in the writings on temporality by philosopher, Martin Heidegger. Her goal is to establish aphilosophical framework for developing practical approaches to teaching art to secondarystudents that address the difference in temporal perception of students with ADHD in an effort tocreate a more inclusive learning environment.